Pesticides and Their Effects on Gut Microbiota: A Comprehensive Review of Environmental and Health Consequences - Nsaif, Ayat Abd-Aljaleel; Aljawhar, Nooralhuda Mundher; Jassim , Sara; Nazar, Zeyad (Medical Science Journal for Advance Research, 2024)
An increasing use of pesticides in agriculture is considered as the dangerous hazard to environment, human health, and sustainability. The effects of pesticides on organisms include decline in the amount of phytoplankton and zooplankton, development of resistance in pests and negative impacts on pollinators. These chemical residues too interfere with the biogeochemical cycles, reduce the microbial count in the soil, and are anti-neo plastic and carcinogenic in nature in different species. Concerning human health effects, the exposure to these chemicals cause cancer, deterioration of neurodevelopment, reproductive disorders as well as immune disorders. Besides, the action of pesticides is aimed at destroying both the beneficial bacteria of the gut microbiota, thus causing obesity and diabetes. The measures required for these problems include regulation and farmer awareness and schooling to stop the contamination from piling up in water bodies. Some strategies include microbial degradation, pesticide degradation and improvement of the population of microorganisms in the soil. Organic farming and sound policies are important to maintain and improve the earth’s condition, uphold the companies’ standards set by the legal frameworks, and sustain the quality of life. Therefore, the impacts of pesticides on microbiota and the interactions of hosts and microbes need to be analyzed to devise appropriate solutions. These efforts are very useful for dealing with possible health threats and ensuring environmentally friendly farming.